The Curve Visible on the Campbell-Robson Chart Is Not the Contrast Sensitivity Function - Tardif, Jessica; Watson, Marcus R.; Giaschi, Deborah; Gosselin, Frédéric (Frontiers in Neuroscience, 2021)
The Campbell-Robson chart is a highly popular figure used in psychophysics and visual perception textbooks to illustrate the Contrast Sensitivity Function (CSF). The chart depicts a grating which varies logarithmically in spatial frequency (SF) from left to right and in contrast from bottom to top. Campbell’s and Robson’s (1964) intuition was that the boundary between the grating and the homogeneous gray area (below threshold) would trace the shape of the observer’s own CSF. In this paper, we tested this intuition. A total of 170 participants (96 adults and 74 children) adjusted the four parameters of a truncated log-parabola directly onto a Campbell-Robson chart rendition and completed a gold-standard CSF evaluation. We hoped that this procedure which requires a mere three clicks on the computer mouse, would speed up the measurement of the CSF to under a minute. Unfortunately, the only parameter of the truncated log-parabola fitted to the gold-standard CSF data that could be predicted from the Campbell-Robson chart data was the peak sensitivity for the adult participants. We conclude that the curve visible on the Campbell-Robson chart cannot be used practically to measure the CSF.